A review identifying the effectiveness of minimum quantity lubrication (MQL) during conventional machining - Boswell, Brian; Islam, Mohammad Nazrul; Davies, Ian; Ginting, Y.; Ong, A. (Springer, 2017)
Government legislation and public opinion are the main drivers behind the movement of manufacturing companies towards sustainable production. Fundamentally, companies want to avoid future financial penalties and the industry is therefore under pressure to adapt new techniques and practices in order to become environmentally friendly. The cost efficiency of metal cutting operations is highly dependent on accuracy, excellent surface finish and minimized tool wear and, to this end, has traditionally made abundant use of cutting fluid in machining operations. However, these cutting fluids have been a major contributor to environmental and health issues. In recent years, an enormous effort to eradicate these adverse effects has been made with one important focus being the implementation of minimum quantity lubrication (MQL). In the present work, the authors have reviewed the current state of the art in MQL with a particular focus on drilling, turning, milling and grinding machining operations. Overall, it is concluded that MQL has huge potential as a substitute for conventional flood cooling.